Comparative response of Callosobruchus maculatus (Fab.) (Coleoptera: Chysomelidae) to Momordica charantia and Acalypha wilkesiana powders in stored cowpea (Vigna unguiculata) (Walp.) - Adeboye, Oyewale Rufus; Oni, Mercy Olayinka; Adesina, Jacobs Mobolade (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
Post-harvest preservation of cowpea in developing countries has been a major challenge owing to Callosobruchus maculatus infestation. The study compares response of C. maculatus (F) to Momordica charantia and Acalypha wilkesiana powders in stored cowpea seeds under laboratory atmosphere. Five pairs of freshly emerged C. maculatus adults were introduced into Petri-dish containing 20 g of cowpea admixed with 0.2, 0.4, 0.6 and 0.8 g of each plant powder, replicated thrice and arranged in a complete randomization design. Adult mortality was recorded at 24 h interval for 5 days, oviposition was recorded after 48 h. While newly emerged insects were recorded 30-35 days after infestation and weight loss was also determined. The treatments showed significant increase in C. maculatus adult mortality as the time of exposure and dosage increases, with highest values (90 and 100% for A. wilkesiana and M. charantia, respectively) at 120 h of exposure and 0.8 g dosage level. At 0.8 g, A. wilkesiana (66.3) and M. charantia (63.0) treated seeds recorded significantly lower number of eggs laid. Similar trend was equally observed for adult emergence and percentage weight loss. The study revealed that both plants had significant insecticidal effects and clearly showed that M. charantia was more effective than A. wilkesiana, but did not show higher significant differences in all the parameters assessed. This indicated that these plant powders have prospective to safeguard cowpea seeds in store from C. maculatus infestation and damage. Therefore, these plant should be included in the Integrated Pest Management Strategies for cowpea storage by small scale farmers.